Structural and Optical Properties of Nd3+ Doped Lead Borotellurite Glass Containing Silver - Abdullah, Mardhiah; Yahya, Norihan; Kasim, Azman; Fatimah Saipuddin, Siti (International Journal of Engineering and Technology, 2018)
Nd3+ doped lead borotellurite glasses which contained silver had been prepared successfully by using conventional melt-quenching method with the chemical composition of (69.5-x)TeO2-20B2O3-10PbO-0.5Nd2O3-xAgNO3 (where x = 0, 0.5, 1.0, 1.5, 2.0 and 2.5 mol%) and varied silver nitrate content. The structural properties had been studied through X-ray diffraction (XRD) analysis and Fourier Transform Infrared (FTIR) spectroscopy. Meanwhile, the optical properties of the glass samples had been characterised by Shimadzu UV-1800 UV-Vis spectrophotometer in the range of 190 â€“ 1100 nm where the absorption peaks were obtained and band assignments of each peak were determined from the absorption spectra. The XRD pattern had been used to confirm the amorphous nature of the glass samples. There was no sharp peak being observed in XRD pattern of the glass samples which had confirmed the amorphous nature of the glass. FTIR spectra were used to analyse the functional groups that existed in the glass samples. They had revealed the presence of or , , , BO4 and the characteristics of the hydrogen bond in the prepared glass samples.Â